Analisis komponen fisik dan percaya diri terhadap kemampuan menggiring bola dalam permainan sepakbola murid SD di Kabupaten Barru - Hasbunallah Hasbunallah; Hasyim Hasyim (Seminar Nasional LP2M UNM, 2019)
This research aimed to know the physique components and self-confidence toward the ability of dribble a ball in football game of students at SDN Madello, Barru.  This research was a descriptive research with two variables used in this research, they were: independent variable which were physique components (balance, speed, and agility) and self-confidence. While dependent variable was the ability to dribble a ball.The population of this research was all of the boys students in class IV and V at SDN Madello, Barru with the numbers were 30 students. The technique to take sample that was used in this research was purposive sampling technique. Purposive sampling technique is “the determination of the sample with a particular consideration”.  From the results of the determination of the sample, the researcher took the boys students in class IV and V were 30 students. Date analysis technique was a single correlation (r) and binary correlation (R) using the SPSS Version System 20.00 at significant level 95% or (α) = 0.05. This research was done in SD N Madello, Barru Jln. Sultan hasanuddin Makassar 110 km. Madello. Balussu, Barru. Based on the data analysis, it is obtained: (1) there was a significant contribution to physique components toward the ability of the dribble a ball in football game of students at SDN Madello, Barru with value R count (Ro) = 0.765 (P (0.000) > 0.05) with the value of the contribution amounted to 58.5%. (2) There was a significant contribution to confidence toward the ability of the dribble a ball in football game of students at SDN Madello, Barru with value R count (Ro) = 0.705 (P (0.000) > 0.05) with the value of the contribution amounting to 50.2%. (3) There was a significant contribution to physique components and self- confidence toward the ability of the dribble a ball in football game of students at SDN Madello, Barru. It was proved the value of R (Ro) count = 0.865 (P (0.000) < 0.05) with the value of the contribution amounted to 74.9%.